Clinical case of imported tropical malaria in a teenager - A. L. Bondarenko (LLC "Diagnostics and Vaccines", 2023)
The article presents a case of imported tropical malaria in a 15-year-old girl who returned from the United Republic of Tanzania 5 days before the onset of the disease. The disease began with an increase in body temperature to 38-40°С, catarrhal phenomena. From the 3rd day of illness, abdominal pains, vomiting, loose stools joined. Despite an earlier request for medical help (the 2nd day of illness) and a timely epidemiological history, the patient was diagnosed with tropical malaria on the 6th day of illness, when complications of the disease developed. Late initiation of adequate therapy led to death from multiple organ failure on the 7th day of illness.